2005
DOI: 10.1144/jm.24.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Early Carboniferous (Late Tournaisian–Early Viséan) ostracods from the Ballagan Formation, central Scotland, UK

Abstract: Abstract. The Ballagan Formation (Late Tournaisian–Early Viséan) of central Scotland yields an ostracod fauna of 14 species in ten genera, namely Beyrichiopsis, Cavellina, Glyptolichvinella, Glyptopleura, Knoxiella, Paraparchites, Sansabella, Shemonaella, Silenites and Sulcella. The ostracods, in combination with palynomorphs, are important biostratigraphical indices for correlating the rock sequences, where other means of correlation, especially goniatites, conodonts, foraminifera, brachiopods or corals are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Siliciclastic sediment, sourced mainly from the highlands to the north was deposited in prograding alluvial to lacustrine deltaic systems, with infrequent marine transgressions (Browne et al 1999). A study of the older (early Mississippian, Courceyan) Ballagan Formation demonstrated ostracods in hypersaline and brackish water bodies (Williams et al 2005(Williams et al , 2006, associated with possible freshwater to brackish algal palynomorphs (Stephenson et al 2004a,b).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Siliciclastic sediment, sourced mainly from the highlands to the north was deposited in prograding alluvial to lacustrine deltaic systems, with infrequent marine transgressions (Browne et al 1999). A study of the older (early Mississippian, Courceyan) Ballagan Formation demonstrated ostracods in hypersaline and brackish water bodies (Williams et al 2005(Williams et al , 2006, associated with possible freshwater to brackish algal palynomorphs (Stephenson et al 2004a,b).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…7) with many other ostracod species (Table 3) and are considered to be eurytopic. Cavellina is known for its marginal marine to brackish-water tolerance in Carboniferous environments (Robinson, 1978;Williams et al 2005Williams et al , 2006. Many Mississippian Shemonaella species are interpreted as marine (for example, Crasquin, 1985;Dewey, 1983), but some are considered as brackish (Tibert & Scott, 1999).…”
Section: B Type 2 Assemblage: Marginal Marinementioning
confidence: 99%
See 2 more Smart Citations
“…Ostracodes, microscopic crustaceans (usually 1-2 mm), with a distinctive bivalved carapace, are widely used in palaeoecology and biostratigraphy because of their relatively short stratigraphic ranges and high abundance in shelf sequences , Williams et al 2005, Tinn et al 2006. The systematics of recent ostracodes is based on soft body anatomy and the carapace features are of secondary importance.…”
mentioning
confidence: 99%